A Knowledge Analysis of the Implementation of STEM-Based Learning of Prospective Chemistry Teachers - Viqri Rolanda; Muhammad Adlim; Muhammad Syukri (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
STEM is one of the students' guides to have the mindset and ability to create an innovative and creative product that is useful for industry or everyday life. As prospective teachers, the students of chemistry education are expected to apply STEM-based learning at schools. Therefore, this study focuses on investigating their knowledge of implementing STEM-based learning. The respondents of this study were students of chemistry education who were prospective teachers and had taken the internship class. Meanwhile, 69 participants fill in the online questionnaire. This study employed a questionnaire and a multiple-choice test with case questions to create a new product. Before applying the questionnaire and test instruments, their contents were validated and tested. The data were analyzed by employing quantitative descriptive analysis. This study reveals that the students' have an average score of STEM knowledge by 3.11 (77.75%), a moderate category of STEM domains by 3.49 (87.25%), STEM indicators by 3.03 (75.75%), and STEM-based learning by 2.81 (70.25%). Meanwhile, the score of students’ knowledge of learning-based STEM is 65.22 and is categorized as moderate. These results consist of mathematical domains score by 34.87 (enough), techniques by 46.38 (enough), planning and implementation by 49.28 (enough), creativity & innovation by 57.97 (moderate), evaluation by 63.77 (medium), technology by 73.91 (medium), a collaboration by 88.41 (high), science by 89.86 (high), and communication by 98.55 (high).